Practitioner's Guide to Latent Class Analysis: Methodological Considerations and Common Pitfalls - Sinha, Pratik; Calfee, Carolyn S; Delucchi, Kevin L (Critical care medicine, 2021)
Latent class analysis is a probabilistic modeling algorithm that allows clustering of data and statistical inference. There has been a recent upsurge in the application of latent class analysis in the fields of critical care, respiratory medicine, and beyond. In this review, we present a brief overview of the principles behind latent class analysis. Furthermore, in a stepwise manner, we outline the key processes necessary to perform latent class analysis including some of the challenges and pitfalls faced at each of these steps. The review provides a one-stop shop for investigators seeking to apply latent class analysis to their data.